(untitled) (Albayan Scientific Journal, 2023)
The primary goals of this study are to design an oscillation generating circuit, to demonstrate how to entirely prevent chaotic emerging in the output circuit. Additionally, the study investigates the chaotic state of electronic circuits using a chaotic oscillator circuit and the time-delay feedback theory, which allows for the control of chaos, maintains the system’s equilibrium, and eliminates chaos. Simulation results that are displayed in MATLAB are used to support the analysis